Coagulation factor activity patterns of venom-induced consumption coagulopathy in naturally occurring tiger snake (Notechis scutatus) envenomed dogs treated with antivenom. (15th July 2020) - Eramanis, Louis Mark; Woodward, Andrew; Courtman, Natalie; Hughes, Dez; Padula, Andrew; Winkel, Kenneth D.; Boller, Manuel
Abstract: Background: Venom-induced consumption coagulopathy (VICC) from tiger snake ( Notechis scutatus ) envenomation results in a dose-dependent coagulopathy that is detectable on coagulometry. However, individual coagulation factor activities in dogs with tiger snake envenomation have not been determined. This study aimed to characterise VICC and the time course of recovery in tiger snake envenomed dogs and to investigate an association between tiger snake venom (TSV) concentrations and factor activity. Methods: This was a prospective, observational, cohort study. The study cohort was 11 dogs of any age, breed, sex, body weight >10 kg, confirmed serum TSV on ELISA and treated with antivenom. Blood was collected at enrolment before antivenom administration, then at 3, 12 and 24 h after antivenom administration. Tiger snake venom concentrations were detected with a sandwich ELISA. Fibrinogen was measured using a modified Clauss method, and coagulation factors (F) II, V, VII, VIII and X were measured with factor-deficient human plasma using a modified prothrombin (PT) and activated partial thromboplastin (aPTT) method. Linear mixed models, with multiple imputations of censored observations, were used to determine the effect of time and TSV concentration on the coagulation times and factor activity. This cohort was compared to 20 healthy controls. Results: At enrolment, there were severe deficiencies in fibrinogen, FV and FVIII, with predicted recovery by 10.86, 11.75 and 13.14 h after antivenom, respectively. There were modest deficiencies in FX and FII, with predicted recovery by 20.57 and 32.49 h after antivenom, respectively. No changes were detected in FVII. Prothrombin time and aPTT were markedly prolonged with predicted recovery of aPTT by 12.58 h. Higher serum TSV concentrations were associated with greater deficiencies in FII, FV and FVIII, and greater prolongations in coagulation times. The median (range) serum TSV concentration was 57 (6–2295) ng/mL. Conclusions: In tiger snake envenomed dogs, we detected a profound, TSV-concentration-related consumption of select coagulation factors, that rapidly recovered toward normal. These findings allowed further insight into tiger snake VICC in dogs. Highlights: Tiger snake envenomed dogs develop venom-induced consumption coagulopathy. Coagulation factor activities are depleted in tiger snake envenomed dogs. Higher venom concentrations result in lower coagulation factor activities. Venom concentrations in tiger snake envenomed dogs are noteworthy.